Novel chitosan/polyvinyl alcohol/talc composite for adsorption of heavy metals and dyes from aqueous solution - Kalantari, Katayoon; Afifi, Amalina Muhammad (Taylor & Francis, 2018)
In this study, adsorption capability of chitosan/polyvinyl alcohol/talc composite (CPTC) in removal of Congo red, Methyl orange, Pb2+, and Cr6+ was evaluated. CPTC was characterized using Fourier transfer infrared spectroscopy, field emission scanning electron microscope, X-ray diffraction, thermogravimetric analysis, and weight loss test. Flocculation was the main phenomena in Congo red removal for 100 mg/L and in Methyl orange for <100 mg/L. The removal amounts of Pb2+ and Cr6+ were 96% and close to 100% up to 200 mg/L, and 88% and 92% at 400 mg/L, respectively. Langmuir model demonstrated better results in describing the heavy metals removal. Moreover, it was found that kinetics followed a pseudo-second-order equation.